Improvement of the short channel effect in PMOSFETs using cold implantation. (October 2016) - Lee, Suk Hun; Park, Se Geun; Jeong, Seong Hoon; Jung, Hyuck-Chai; Kim, Il Gweon; Kang, Dong-Ho; Nam, Hyo-Jik; Kim, Dae Jung; Lee, Kyu Pil; Choi, Joo Sun; Jung, Woosuk; Park, Yongkook; et al.
Graphical abstract: Highlights: The effect of cold-implantation was investigated in terms of dopant diffusion. VTH roll-off, Ioff increment, and contact resistance was improved by cold-IIP. The standby current at a short tPD was reduced effectively for the cold-IIP case. Abstract: In this paper, to suppress transient enhanced dopant diffusion and improve short channel effects, cold implantation (cold-IIP) was applied to contact PLUG implantation in P-channel metal oxide semiconductor field effect transistors (PMOSFETs). A shallow dopant profile was formed by the suppression of transient enhanced diffusion (TED) due to the reduction of end-of-range (EOR) defects. Threshold voltage roll-off and off current (Ioff ) increment, which are caused by a reduction in the distance between the gate and contact, were improved compared with room temperature implantation (RT-IIP). Additionally, the drain induced barrier lowering was improved, and the on-current improvement was attributed to reducing the contact resistance through the reduction of EOR defects. The contact resistance was reduced by ∼6% of the RT-IIP. In the DRAM device, the standby current at a short propagation delay time (tPD ) was reduced effectively due to the decrease in the Ioff and contact resistance for the cold-IIP case.